Opportunities of prevention of asthma exacerbation induced by respiratory infection in children using bacterial lysates - T.R. Umanets; V.F. Lapshyn; О.О. Rudnev (Zaslavsky O.Yu., 2020)
The infectious factor is known to play an important role not only as a trigger for asthma exacerbation, but also an essential factor for the formation of the disease. Children with asthma are 6.2 times more likely to have acute respiratory diseases than healthy children. This is due to altered barrier function of the respiratory epithelium and immune antiviral responses. Viruses dominate in the etiological structure of infectious-dependent exacerbations of asthma. The preclinical and clinical studies have shown the effectiveness of an immunomodulatory strategy for the prevention of recurrent respiratory infections in children with asthma using bacterial mechanical lysates.